2014
DOI: 10.2105/ajph.2013.301694
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Harmful Content on Outdoor Advertising in Los Angeles: Land Use, Community Characteristics, and the Spatial Inequality of a Public Health Nuisance

Abstract: This study provides evidence of the potential for land-use decisions to result in spatially inequitable health impacts. Although dictating the placement of outdoor advertising through zoning may seem sensible, such a decision might have the unintended consequence of disadvantaging the well-being of local communities. Neighborhood factors require more contextually nuanced public health and land-use policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 42 publications
5
39
0
Order By: Relevance
“…17 Although the patterns reported here may not generalize to all American cities, the results are consistent with other works showing disparities in outdoor obesity-related advertising found in Los Angeles, New Orleans, Philadelphia, Austin, and New York. 7,9,10 It is important to point out that the present study does not address the gap in the literature surrounding the causal link between unhealthy advertising and obesity and more work is needed in this area. Future research should also investigate the ways in which the broader food information environment, or macro environments, shapes food choice in much the same way that research has confirmed that micro environments, like interiors of restaurants and grocery stores, are designed to encourage unhealthy food choices and overeating.…”
Section: Resultsmentioning
confidence: 91%
“…17 Although the patterns reported here may not generalize to all American cities, the results are consistent with other works showing disparities in outdoor obesity-related advertising found in Los Angeles, New Orleans, Philadelphia, Austin, and New York. 7,9,10 It is important to point out that the present study does not address the gap in the literature surrounding the causal link between unhealthy advertising and obesity and more work is needed in this area. Future research should also investigate the ways in which the broader food information environment, or macro environments, shapes food choice in much the same way that research has confirmed that micro environments, like interiors of restaurants and grocery stores, are designed to encourage unhealthy food choices and overeating.…”
Section: Resultsmentioning
confidence: 91%
“…In terms of ads for other beverages, and for food items, one prior study showed that outdoor ads for unhealthful items (those high in calories and low in nutrition) represented 18.9% of the total ad space in African American communities: a percentage more than twice that seen in white communities [6]. Latino communities, particularly those dense with young people, also showed disproportionate unhealthful-food advertising, and Latino communities with "multiple risks" (income insecurity, low-education, and high youth representation) had more than four times the percentage of ads for "addictive behaviors" (e.g., alcohol) than white communities [6].…”
Section: Discussionmentioning
confidence: 99%
“…Latino communities, particularly those dense with young people, also showed disproportionate unhealthful-food advertising, and Latino communities with "multiple risks" (income insecurity, low-education, and high youth representation) had more than four times the percentage of ads for "addictive behaviors" (e.g., alcohol) than white communities [6]. These results are consistent with the present study that showed "less-healthful" foodor-beverage ads-specifically those in Spanish, directed at youth, and/or featuring minorities-directly correlated with poverty, lower high-school graduation rates, higher percentages of Hispanic residents, and/or higher percentages of children in surrounding residential areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Simultaneously, outdoor advertising has long been viewed by many as a visual nuisance, an affront to the beauty of the landscape, 3 and a contributor to neighborhood effects that are detrimental to the health and well-being of individuals and communities, particularly communities of color. 4 The challenges generated by demands for consumption and the visual quality of place make outdoor advertising a particularly interesting case study in the evolution of land use regulation in the United States. The efforts of Los Angeles and other cities to regulate outdoor advertising based on zoning are not new.…”
Section: Introductionmentioning
confidence: 99%